Closed-Horizontal Rotating Burner Development for Optimizing Plam Shell Charcoal (PSC) Production - Dafit Feriyanto; Supaat Zakaria; Sagir Alva; Hadi Pranoto; Andi Firdaus Sudarma; Albert Phak Jie Wong (International Journal of Advanced Technology, 2020)
Activated Carbon (AC) was produced through several stages such as carbonization, crushing and activation process. The critical part of AC production was located at carbonization process due to burner issues that need to complete burning in short time, appropriate temperature and low cost. Therefore, this research focus on developing burner which called by closed-horizontal rotating burner. The dimension of the burner was 65 x 790 mm (D x L) wih the capacity of 30 kg/carbonization process. This burner need 1 hour for complete burning of palm shell to palm shell charcoal (PSC). Several analysis were conducted such as stress, displacement, factor of safety and thermal analysis. because this burner involved in rotation motion and high temperature operation. Physical properties has been measured which consists of moisture content (3.8-5%), ash content (7.7-8%), volatile content (53.7-56.6%) and fixed carbon content (31.3-34.7%). It can be summarized that this burner was very effective to produce PSC with short time carbonization process, low cost and complete charcoal production.